State regulation and educational segregation in the Province of Buenos Aires - Veleda, Cecilia (Education Policy Analysis Archives, 2014)
This article examines how the legislation of the Province of Buenos Aires contributes to the segregation of school enrolments, defined as the separation of students into unequal educational circuits according to their socio-economic background, offering different experiences of socialization, learning conditions and knowledge. The study analyzed legislation and how the work of intermediate level authorities (supervisors, school councils, and municipal governments) influences the distribution of students, teachers and material resources, and some of the pedagogic proposals of different schools. The article concludes that, in certain cases, provincial legislation favors school segregation through an unjust allocation of students, teachers and material resources. The mentioned legislation also contributes to segregation in an indirect way, by opening up ample possibilities for agents at “the base” of the educational system – intermediate level authorities, school principals and families – to act and influence the way in which the mentioned elements are distributed.